1999
DOI: 10.1016/s0014-5793(99)00182-9
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate changes of polyamine metabolism regulatory proteins during the cell cycle of normal human dermal fibroblasts

Abstract: In human dermal fibroblasts, brought to quiescence (G H ) by serum starvation, the S phase peaked 24 h and G P /M phases 36 h after serum re-addition. Under the same conditions, ornithine decarboxylase mRNA peaked at 12 h, decreased markedly in S phase and remained low until 48 h. Conversely, ornithine decarboxylase antizyme transcript dropped to its lowest level at 12 h, while reaching its highest values between 24 and 48 h. Ornithine decarboxylase activity followed essentially the pattern of its mRNA, but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
3
32
1
7
Order By: Relevance
“…7,28 This relationship is also observed in skeletal muscle, where ODC is upregulated by the androgen receptor, promoting cell proliferation and delayed differentiation, both of which are features of tumor formation. 29 Even though some authors have reported how polyamine pathway controls cell cycle, 30 ODC functional contribution in prostate tumor initiation has not been fully explored to date.…”
Section: Discussionmentioning
confidence: 99%
“…7,28 This relationship is also observed in skeletal muscle, where ODC is upregulated by the androgen receptor, promoting cell proliferation and delayed differentiation, both of which are features of tumor formation. 29 Even though some authors have reported how polyamine pathway controls cell cycle, 30 ODC functional contribution in prostate tumor initiation has not been fully explored to date.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from several laboratories have shown that perturbation of the levels of antizyme, ODC, or polyamines can affect cell cycle progression (9,14,27,28). However, the mechanisms by which antizyme may influence the cell cycle have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This fact and the proven importance of ODC in cell transformation could suggest that putrescine could serve not only as a requested substrate for spermidine (and spermine) synthesis but also as a regulatory signal of cell proliferation. It has been shown that peaks of putrescine occur in different phases of the cell cycle (29,75). Furthermore, putrescine stimulates tyrosine phosphorylation by tyrosine kinases and the expression of the nuclear oncogenes c-fos and c-jun (35).…”
Section: Model Predicts Compensatory Mechanisms To Keep Polyamine Hommentioning
confidence: 99%